Comparisons Extensions of Plastic zones for Micro-indentation of a Rigid Wedge to a semi-infinite block by Finite Element Analysis and Numerical Slip-line Field Techniques - Biswas, Arup K.; Das, Santanu; Das, Sanjoy (Indian Science Cruiser, 2019)
The present work compares the extension of plastic zones when a rigid indenter is indented to a semi-infinite block of Mild Steel by finite element analysis (FEA) and numerical slip-line field (SLF) technique. The semi-apex angle of the wedge is varied from 10Â° to 80Â° with different friction conditions. The previous works of the present authors showed that the lip profiles of deformed material around the wedge are nonlinear in nature. The results obtained from the present analysis, showed that extend of plastic zones obtained by SLF with parabolic lip and FEA are very close. Hence, the original proposition of the previous works by present authors that the nature of lip profile is non-linear is again proved in this present work.